The dual penal empire: Emergency powers and military courts in Palestine/Israel and beyond - Ben-Natan, Smadar (Punishment & society, 2021)
This article explores the duality of emergency powers and criminal law in old and new formations of empire. Set against the backdrop of the US “war on terror,” I link discussions around current articulations of empire and the treatment of “enemy combatants,” illuminating new connections between empire, emergency, and “enemy penology.” Focusing on Palestine/Israel, I explore the duality created by emergency powers and criminal law from the late British Empire to contemporary Israel/Palestine as an “imperial formation.” Through a genealogy of emergency legislation, military courts, and two case studies from the 1980s Israel, I show how emergency powers constitute a penal regime that complements ordinary criminal law through prosecutions of racialized enemy populations under a distinct exclusionary and punitive legality. Building on Markus Dubber's Dual Penal State, I demonstrate how the—openly illiberal—dual penal empire (i) suppresses political resistance (insurgency, rebellion, and terrorism) and (ii) institutionalizes enemy penology through emergency statutes and military courts. Thus, in imperial formations, such as Israel and the US—which deny their illiberal features—emergency powers are framed as preventive security and denied as part of the penal system, while enemy penology operates in plain sight.